Comparison of surgical invasiveness, hidden blood loss, and clinical outcome between unilateral biportal endoscopic and minimally invasive transforaminal lumbar interbody fusion for lumbar degenerative disease: a retrospective cohort study - Xinle Huang; Wenkai Wang; Guangxing Chen; Xiangchen Guan; Yue Zhou; Yu Tang (BMC Musculoskeletal Disorders, 2023)
Abstract Background Currently, hidden blood loss (HBL) has been paid more and more attention by spine surgeons. Simultaneously, it has been the effort of spine surgeons to explore more advantages of minimally invasive surgery. More and more articles have compared unilateral biportal endoscopic lumbar interbody fusion (BE-LIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). But so far, there is no HBL comparison between BE-LIF and MIS-TLIF. This study aims to compare the surgical invasiveness, hidden blood loss, and clinical outcome of BE-LIF and MIS-TLIF and to provide insight regarding minimally invasive surgery for lumbar degenerative disease (LDD). Methods We enrolled 103 eligible patients with LDD who underwent BE-LIF (n = 46) and MIS-TLIF (n = 57) during August 2020–March 2021. We collected data, including demographics, perioperative haematocrit, operative and postoperative hospital times, serum creatine kinase (CK) and C-reactive protein (CRP) levels, and hospitalization costs. Total and hidden blood loss was calculated. Clinical outcomes were assessed using a visual analogue scale (VAS) score for back and leg pain, Oswestry Disability Index (ODI), modified MacNab criteria, fusion rate, and complications. Results Basic demographics and surgical data were comparable. The CRP and CK levels were generally lower in the BE-LIF than in the MIS-TLIF group, especially CRP levels on postoperative day (POD) three and CK levels on POD one. True total blood loss, postoperative blood loss, and hidden blood loss were significantly reduced in the BE-LIF group compared with the MIS-TLIF group. Postoperative hospital times was statistically significantly shorter in the BE-LIF group. The VAS pain and ODI scores improved in both groups. At three days and one month, the VAS lower back pain scores were significantly better after BE-LIF. Clinical outcomes did not otherwise differ between groups. Conclusions Compared with MIS-TLIF, BE-LIF has similar medium and short-term clinical outcomes. However, it is better regarding surgical trauma, early lower back pain, total and hidden blood loss, and recovery time. BE-LIF is an adequate option for selected LDD.